Toxic gas whisperers: Sensing dynamics of pristine and alloyed Cu nanoclusters - Kumbagiri Madhavi; Namrata A Tukadiya; Prafulla Jha; Riddhi Sainda; Shweta D. Dabhi; Venu H. Mankad (Chemical Physics Impact)
The present study investigates the interactions of environmental pollutants, such as CO, NO, and NH₃, with copper nanoclusters Cuₙ (n = 2–6), given their significant applications in catalysis and gas sensing. Among the nanoclusters studied, Cu₄ and Cu₆ demonstrated the strongest interactions with toxic gases and exhibited aromatic properties. When alloyed with silver (Ag) and nickel (Ni) to form bimetallic nanoclusters (Cu₃M and Cu₆M, where M = Ag, Ni), these clusters displayed enhanced catalytic activities for gas sensing, storage, and removal of harmful chemicals. The study calculated the structural stability, infrared activity, formation energy, and binding energies. Cu₄ and Cu₆ clusters substituted with Ag and Ni yields binding energy values of -2.82 eV, -3.26 eV, -3.32 eV, and -3.62 eV, respectively. These results indicate that interactions with transition metals (TMs) are energetically favorable. The calculated adsorption energies for CO gas on pristine Cu₄, Cu₃Ag, and Cu₃Ni were determined to be -0.60, -0.40, and -0.56 eV, respectively, indicating weak physisorption in the case of Cu₃Ag. Similarly, the adsorption energies for NO gas on Cu₄, Cu₆, and Cu₃Ag were -0.79, -0.21, and -0.77 eV, respectively. Furthermore, NH₃ adsorption on Cu₃Ag resulted in an energy of -1.11 eV, suggesting stronger interaction compared to other gases. The optimal adsorption energy obtained suggests promising recovery times for CO and NO on Cu₃Ni and Cu₆, measured at 2.20 and 2.70 s, respectively, underscoring their effectiveness in molecular sensing. For NH₃, the recovery time of 3.85 s highlights the potential of both doped and pristine clusters for efficient NH₃ removal from the environment. Additionally, the study analysed the density of states (DOS), revealing significant changes in molecular orbitals, particularly in the HOMO-LUMO gap, which further supports the enhanced reactivity of the nanoclusters.